Plant chloroplast stress response: insights from mass spectrometry metabolites analysis - Cheng, Si; Xu, Jiawei; Wu, Siqi; Li, Qun; Mi, Jianing (Frontiers in Plant Science, 2025)
Plant chloroplasts produce excess reactive oxygen species (ROS) during photosynthesis, particularly under biotic and abiotic stress conditions. These adverse environmental stresses lead to significant alterations in various cellular components, especially within the chloroplast, which serves as a key stress-sensor organelle. The stress response of chloroplasts can trigger plastid-to-nucleus retrograde signaling and enhance the biosynthesis of biologically active compounds and phytohormones, which are mechanisms that aid plants in acclimating to environmental stress. While ROS act as signaling molecules to help re-adjust cellular metabolic homeostasis, they also risk damaging chloroplasts’ structural and functional integrity. Recent research on stress-induced plant metabolism has provided new insights into the chloroplast’s stress response. In particular, advancements in mass spectrometry (MS) techniques have expanded our understanding of how oxidative stress affects plants through metabolomics analyses of metabolites involved in this process. Here, we emphasize the MS-based profiling of lipids, apocarotenoids, and phytohormones linked to ROS-triggered processes in plants. Moreover, we discuss the plants’ metabolic responses to abiotic stress. Finally, we outline future directions for chloroplast stress research. We advocate for integrating MS-based metabolomics with biochemical and molecular genetic approaches to discover new signaling molecules and identify interconnected signaling components that function across multiple chloroplast signaling pathways.